Big love. The complete second season [videorecording (DVD)] - Paxton, Bill; Tripplehorn, Jeanne, 1963-; Sevigny, Chloë; Goodwin, Ginnifer; Stanton, Harry Dean, 1926-2017; Seyfried, Amanda (HBO Video, 2007)
"Season two ... finds the modern-day polygamist Bill Henrickson and his three wives struggling to pick up the pieces after first wife Barb's outing at the Beehive Mother of the Year Ceremony. Second wife Nicki, learning that it was her father, Roman Grant, Prophet of the Fundamentalist Juniper Creek compound, who betrayed them, battles conflicting family loyalties. And third wife Margene, newly pregnant, fights for a bigger piece of the family pie with an eye toward bringing a new wife and confidante into the fold. All of this domestic drama plays out against the backdrop of Bill's new, visionary business plans--which put him into direct conflict with his father-in-law and some rather unexpected and unsavory antagonists."--Container.